2007
DOI: 10.1177/1934578x0700200108
|View full text |Cite
|
Sign up to set email alerts
|

New Neuritogenic Steroid Glycosides from the Vietnamese Starfish Linckia Laevigata

Abstract: Two new steroid glycosides, linckosides L1 (1) and L2 (2), were isolated, along with the previously known echinasteroside C (3) from the ethanolic extract of the Vietnamese blue starfish, Linckia laevigata. The structures of the new compounds were elucidated by spectroscopic methods (mainly 2D NMR) and chemical transformations. Lifetime observations and analyses of silver impregnated preparations on the culture of neuroblastoma C-1300 cells showed that glycosides 1, 2, and 3 are capable of inducing neuronal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…The neuritogenic activity of starfish polar steroids in living NB cells can be detected beginning at the second day of cultivation, as we have described previously [11,12,13]. Previous results have demonstrated that a series of polar steroids, including 1 – 3 , manifested significant and nearly identical neuritogenic effects at doses of 2–20 μM, but these effects were slight or even absent at higher concentrations of approximately 40 μM [11].…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The neuritogenic activity of starfish polar steroids in living NB cells can be detected beginning at the second day of cultivation, as we have described previously [11,12,13]. Previous results have demonstrated that a series of polar steroids, including 1 – 3 , manifested significant and nearly identical neuritogenic effects at doses of 2–20 μM, but these effects were slight or even absent at higher concentrations of approximately 40 μM [11].…”
Section: Resultssupporting
confidence: 70%
“…The assays for neuritogenic activity in live cells were performed according to previously described methods [11,12,13]. For experiments involving silver impregnation, the cells were seeded in 6-well plastic plates (2 × 10 4 cells per well) with glass coverslips.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling constant (7.4 Hz) of the anomeric H‐atom corresponded to a β ‐configuration of the glycosidic bond. The C‐ and H‐atom signals and the corresponding coupling constants of monosaccharide unit coincided well with those of the terminal 2‐ O ‐methyl‐ β ‐xylopyranosyl residue . Acid hydrolysis of glycoside 1 with 2 m aqueous CF 3 COOH was carried out to ascertain a stereochemical series of its monosaccharide unit.…”
Section: Resultsmentioning
confidence: 63%
“…lincki was subjected to the sequential separation by chromatography on columns with Polychrom‐1 , silica gel, and Florisil , followed by HPLC on semipreparative Diasfer‐110‐C18 , Discovery C 18 , and analytical Diasfer‐110‐C18 columns to yield the four new steroidal glycosides 1 – 4 and the four previously known glycosides 5 – 8 . The known compounds were identified by comparison of their 1 H‐ and 13 C‐NMR, and MS spectra with those reported for linckoside L1 ( 5 , (3 β ,4 β ,5 α ,6 β ,15 α ,24 S )‐4,6,8,15,24‐pentahydroxycholestan‐3‐yl 2‐ O ‐methyl‐ β ‐ d ‐xylopyranoside) from Linckia laevigata , granulatoside A ( 6 , (3 β ,4 β ,5 α ,6 β ,15 α ,24 S )‐4,6,8,15‐tetrahydroxy‐3‐[(2‐ O ‐methyl‐ β ‐ d ‐xylopyranosyl)oxy]cholestan‐24‐yl α ‐ l ‐arabinofuranoside) from Choriaster granulatus , leviusculoside D ( 7 , sodium (3 β ,6 β ,15 α ,16 β ,22 E ,24 R )‐6,8,16,28‐tetrahydroxy‐3‐[(2‐ O ‐methyl‐ β ‐ d ‐xylopyranosyl)oxy]ergosta‐4,22‐dien‐15‐yl sulfate) from Henricia leviuscula , and echinasteroside B ( 8 , sodium (3 β ,6 β ,15 α ,16 β ,24 R )‐6,8,16,29‐tetrahydroxy‐3‐[(2‐ O ‐methyl‐ β ‐ d ‐xylopyranosyl)oxy]stigmast‐4‐en‐15‐yl sulfate) from Echinaster sepositus .
…”
Section: Resultsmentioning
confidence: 99%